The Creation of Wealth and Value - Yet Another Definition of Entrepreneurship - TAN, Wee Liang (Institutional Knowledge at Singapore Management University, 1994)
It seems strange that we should in this journal be defining entrepreneurship as if it were a philosophy in Raymond W Y Kao’s definitions that emblazons the inside cover of the journal. They are unlike other definitions of entrepreneurship that have focused either on the individual entrepreneur, his or her traits, or a process that ranges from the pre-launch to post-launch stages of a business venture. One might argue that it does not provide a working definition for research in view of its breadth. However, if one were to be open-minded, not dismiss the definitions and examine them, one discovers that they do provide a liberating and all encompassing idea – they supply meaning and purpose to those who seek to put them into practice. The definitions can only be practiced if there is the accompanying attitude changes: wealth creation, value creation and the creation of these in the context of self and not self alone but the world. These attitude changes are the essence of the definitions. It is a liberating set of definitions for they expand the boundaries of entrepreneurship. Entrepreneurship is for everyone who seeks to practice wealth and value creation. It can feature in an individual who is an employee or in a firm where the enterprising culture exists. One is not required to be the founder-owner of new ventures.